2016
DOI: 10.7567/jjap.55.07kf04
|View full text |Cite
|
Sign up to set email alerts
|

Improved highly accurate localized motion imaging for monitoring high-intensity focused ultrasound therapy

Abstract: Visualizing an area subjected to high-intensity focused ultrasound (HIFU) therapy is necessary for controlling the amount of HIFU exposure. One of the promising monitoring methods is localized motion imaging (LMI), which estimates coagulation length by detecting the change in stiffness. In this study, we improved the accuracy of our previous LMI by dynamic cross-correlation window (DCCW) and maximum vibration amount (MVA) methods. The DCCW method was used to increase the accuracy of estimating vibration amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…However, errors were found in the estimated lesions’ size and overtreatment occurred due to system delay after ceasing the HIFU sonication. Qu et al (2016) improved the LMI method by employing a dynamic cross-correlation window, which decreased the RMSE of the estimated coagulation length to 1.69 mm during porcine liver ablation ( N = 49), but increased processing time for displacement estimation from 2.05 ± 0.05 s to 2.64 ± 0.36 s for 28 A-mode scan lines.…”
Section: Introductionmentioning
confidence: 99%
“…However, errors were found in the estimated lesions’ size and overtreatment occurred due to system delay after ceasing the HIFU sonication. Qu et al (2016) improved the LMI method by employing a dynamic cross-correlation window, which decreased the RMSE of the estimated coagulation length to 1.69 mm during porcine liver ablation ( N = 49), but increased processing time for displacement estimation from 2.05 ± 0.05 s to 2.64 ± 0.36 s for 28 A-mode scan lines.…”
Section: Introductionmentioning
confidence: 99%
“…New biomedical applications of this therapeutic method are also being explored, such as hemostasis and gene therapy [4]. Pioneering studies have demonstrated that HIFU, with spatial-peak temporal-average intensities (IsPTa) between 500 and 104 W/cm 2 at the beam focus [5], can produce necrotic lesions in deep-seated tissue through thermal coagulation and cavitation disruption, with minimal damage to the surrounding tissues [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…With different contact forces, the absolute threshold of hearing can be affected by more than 10 dB. 20) Unlike other transducers for mechanical systems using ultrasound [19][20][21][22][23][24][25][26][27][28][29][30][31][32] , a bone-conducted transducer is not used with matching layers or with rigid mounts. International standards on bone-conducted sound transducer calibration reflect the effect of contact force on bone-conducted sound.…”
Section: Introductionmentioning
confidence: 99%